Duty of Fair Representation Recent Attitude in British Columbia and Ontario - MacPhillips, David (Relations industrielles / Industrial Relations, 1981)
This paper discusses how far the duty of fair representation should be broadened in Canada and then argues that the Labour Boards are not the appropriate body to have jurisdiction over such matter.